Power converter for dual-power photovoltaic-grid energy system / Intan Rahayu Ibrahim - Ibrahim, Intan Rahayu (Institute of Graduate Studies, UiTM, 2017)
High frequency switching activities of power electronic devices in the power converter produce switching losses, harmonic distortions and raise high voltage and magnetic stresses in the power converter circuit, consequently affecting the efficiency and quality of output of the converter. In this research study, a new power converter utilizing low fundamental frequency switching technique is being proposed to resolve harmonics distortion issues. This research aims to develop switching and control technique for power converter in dualpower photovoltaic-grid energy system. 21-level cascaded H-bridge multilevel inverter is developed by cascading five of 5-level H-bridges with five separate PV sources. 5-level H-bridge produces high level of output “stepped” voltage with reduced number of power switches. The optimized switching strategy of proposed MhyPSO technique successfully reduced the THD level to 3.94% in the simulation circuit and 6.7% in the hardware circuit. Each of 5-level H-bridges is equipped with the individual boost regulator embedded with MPPT and battery management system.